A new receiver structure for asynchronous CDMA STAR-the spatio-temporal array-receiver. - Affes, S.
We propose a spatio-temporal array-receiver (STAR) for asynchronous code division multiple access (CDMA), using a new space/time structural approach. First, STAR performs blind identification and equalization of the propagation channel from each mobile transmitter. Second, it provides fast and accurate estimates of the number, relative magnitude, and delay of the multipath components. From this space/time separation, STAR reconstructs the identified channel with respect to a partially revealed space/time structure and reduces identification errors by the order of the ratio of the processing gain and the number of paths. Therefore, STAR offers a high potential for increasing capacity, with relatively low computational complexity. Simulations confirm the good multipath acquisition and tracking properties of STAR in the presence of strong interference and fast Doppler
Keywords: STAR; Asynchronous CDMA; Blind equalization; Blind identification; Cellular communications; Code division multiple access; Delay; Fast Doppler; Identification errors; Interference; Low computational complexity; Mobile transmitter; Multipath acquisition; Multipath components; Partially revealed space/time structure; Processing gain; Propagation channel; Receiver structure; Relative magnitude; Simulations; Smart antennas; Space/time separation; Space/time structural approach; Spatio-temporal array-receiver.; Tracking properties